2020
DOI: 10.1097/brs.0000000000003203
|View full text |Cite
|
Sign up to set email alerts
|

Do We Have Adequate Flexion-extension Radiographs for Evaluating Instability in Patients With Lumbar Spondylolisthesis?

Abstract: Study Design. A retrospective cohort study of consecutive patients. Objective. To investigate whether adequate flexion-extension was acquired in standard functional radiographs in lumbar spondylolisthesis. Summary of Background Data. In lumbar spondylolisthesis, flexion-extension radiographs taken in the standing position are most commonly used to evaluate spinal instability. However, these functional radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Mean ST was significantly smaller in CT and MRI compared to each functional radiograph, while there was no difference between indicating a tendency for inadequate flexion due to pain or a sense of insecurity, which could lead to underestimation of lumbar instability ( 25 ). A similar phenomenon has been described by Morita et al, where greater flexion was acquired in functional radiographs if patients were led by hand compared to images where they were not ( 26 ). Leading patients through the motions during radiograph acquisition might help to overcome back pain and mental uneasiness about falling to a certain degree, albeit not being able to fully outweighing muscle tension counteracting segmental movement ( 25 ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Mean ST was significantly smaller in CT and MRI compared to each functional radiograph, while there was no difference between indicating a tendency for inadequate flexion due to pain or a sense of insecurity, which could lead to underestimation of lumbar instability ( 25 ). A similar phenomenon has been described by Morita et al, where greater flexion was acquired in functional radiographs if patients were led by hand compared to images where they were not ( 26 ). Leading patients through the motions during radiograph acquisition might help to overcome back pain and mental uneasiness about falling to a certain degree, albeit not being able to fully outweighing muscle tension counteracting segmental movement ( 25 ).…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, we were able to demonstrate that the comparison of plain radiographs to either CT scans or MRI images is more sensitive for the detection of increased sagittal translation than functional X-rays alone. As there is a multitude of different functional radiographs that lack standardized routines and depend on compliance and effort of patients and examiners alike, different results due to impaired specificity have to be expected ( 18 , 26 , 30 ). Simplifying the diagnostic process reduces interpatient and interexaminer differences and might help avoid misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, 8% of the studies in the present review included a kyphotic angle or posterior opening in flexion in their definition of instability. 22 , 28 , 34 - 41 …”
Section: Discussionmentioning
confidence: 99%
“…16,26,27 Studies have shown that other radiographic protocols might be more sensitive or accurate than standing flexion and extension radiographs. 25,26,[28][29][30] Recently, Liu et al 25 compared flexion-extension radiographs to an upright lateral radiograph and supine MRI (upright-supine method) and showed that the slip percentage difference was significantly higher in the upright-supine method than that observed by the flexionextension method. Other studies support these findings regarding dynamic changes in alignment from upright to supine images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation